Synthesis and characterization of sodium alginate ? graphene oxide aerogel beads obtained via supercritical CO2 drying - Lentz, Lucas (2020)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Alimentos, Florianópolis, 2020.